2021
DOI: 10.1021/acs.joc.1c02024
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Addition of Dialkyl Phosphites to Phthalazin-2-ium Bromide: Synthesis of α-Aminophosphonate Analogues

Abstract: α-Aminophosphonate analogues containing a phthalazine skeleton were efficiently obtained by a new transition-metal-free addition of dialkyl phosphites to phthalazin-2-ium bromide under mild conditions. A mechanistic study using isotope labeling and radical inhibition experiment revealed that the present transformation passes through a nucleophilic addition of dialkyl phosphates, rather than an insertion of P-H to carbenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Scheme 3 Formation of bis-sulfide 5a from thiol 1a in DMSO Therefore, according to literature reports, 37,38 the reaction proceeds by formation of a known intermediate of disulfide 5a via the oxidation of thiols, followed by nucleophilic substitution of diethyl phosphite with the disulfide intermediate to give phosphorothioate 3 (Scheme 4).…”
Section: Letter Synlettmentioning
confidence: 95%
“…Scheme 3 Formation of bis-sulfide 5a from thiol 1a in DMSO Therefore, according to literature reports, 37,38 the reaction proceeds by formation of a known intermediate of disulfide 5a via the oxidation of thiols, followed by nucleophilic substitution of diethyl phosphite with the disulfide intermediate to give phosphorothioate 3 (Scheme 4).…”
Section: Letter Synlettmentioning
confidence: 95%
“…To obtain phosphonylated phthalazine derivatives 843 , Chen and co-workers have developed an addition reaction of H-phosphites 842 to phthalazin-2-ium bromides 841 (Scheme ). This metal-free methodology needs the presence of a base, such as Li 2 CO 3 , to afford the phosphonylated derivatives by nucleophilic addition of dialkyl phosphites, which are favored to undergo phosphonate–phosphite tautomerism in the presence of a base …”
Section: Six-membered Rings: Nonaromatic Aromatic and Benzo-fused Het...mentioning
confidence: 99%
“…This metal-free methodology needs the presence of a base, such as Li 2 CO 3 , to afford the phosphonylated derivatives by nucleophilic addition of dialkyl phosphites, which are favored to undergo phosphonate−phosphite tautomerism in the presence of a base. 424 Trofimov and collaborators have reported that acridines 844 can undergo a nucleophilic addition of secondary phosphine oxides and dialkylphosphites 845 under catalyst-free conditions to obtain the corresponding 9-phosphoryl-9,10dihydroacridines 846 in good yields (Scheme 154). This reaction was applied to the addition of other secondary phosphine chalcogenides with similar results.…”
Section: Tetrahydroisoquinolines and Tetrahydroquinolinesmentioning
confidence: 99%